IMPLEMENTASI ANT-BASED ROUTING ALGORITHM PADA MOBILE AD HOC NETWORK (MANET) - Rahmadani, Safriadi (Journal Information System Development (ISD), 2017)
MANET is a network model cordless (wireless) from mobile devices that can be setup dynamically from anywhere and at anytime without using a fixed network infrastructure. Ease of use and it is without a fixed infrastructure (less infrastructure) makes this model very suitable for use in critical situations, such as in the aftermath of disaster, isolated areas and areas with minimal communications network resources. To maximize the utilization and use of MANET network system, especially on the determination and selection of the best route to a node can connect and transmit the packet from the source node to the destination node to be optimized. This study was done to improve the performance of packet delivery by creating a node that functioned as a gateway and client using routing protocols Ant-Based Routing Algorithm (ABRA) so as to reduce the processing time (overhead) that often occurs in MANET network. Testing is done with a number of different nodes of 10, 20, and 30 nodes, with a bandwidth of 5 Mbps, 5 Mbps and the packet area of 10x10 m. The test results demonstrate the value of performance metrics on throughput and delay have optimal performance and low overhead so that the process of communication in the area of MANET network can take place with the stable.Keywords: Manet, ant-based routing algorithm, networking